Quality education in science and technology (QUEST) : dissemination of the science and technology culture in tertiary education system - Halimaton Hamdan, 1956-; Universiti Teknologi Malaysia. Fakulti Sains. Jabatan Kimia; Annual ASAIHL Seminar on Higher Education for All (1995 : Bangkok, Thailand)
06